Partial Quark-Lepton Universality and Neutrino CP Violation - Jiajun Liao; D. Marfatia; K. Whisnant (Advances in High Energy Physics)
We study a model with partial quark-lepton universality that can naturally arise in grand unified theories. We find that constraints on the model can be reduced to a single condition on the Dirac CP phase δ in the neutrino sector. Using our current knowledge of the CKM and PMNS mixing matrices, we predict -32.4°≤δ≤32.0° at 2σ.